Bactericidal Activity of Colloidal Silver Against Grampositive and Gramnegative Bacteria - I. A. Afonina; L. A. Kraeva; G. YA. Tseneva (Антибиотики и Химиотерапия, 2020)
It was shown that colloidal silver solution prepared In cooperation with the A. F. Ioffe Physical Technical Institute of the Russian Academy of Sciences, had significant bactericidal activity. Stable bactericidal effect on gramnegative microorganisms was observed after their 2-hour exposition in the solution of colloidal silver at a concentration of 10 ppm. Grampositive capsule-forming microorganisms were less susceptible to the colloidal silver solution: their death was observed after the 4-hour exposition in the solution.